2005
DOI: 10.2337/diacare.28.12.2919
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry, Glucose Tolerance, and Insulin Concentrations in Indian Children

Abstract: OBJECTIVE -The purpose of this study was to test the hypothesis that the environment experienced by fetuses of mothers with gestational diabetes mellitus (GDM) and mothers with higher glucose concentrations that are in the normal range causes increased adiposity and altered glucose/insulin metabolism in childhood.RESEARCH DESIGN AND METHODS -Children (n ϭ 630) whose mothers were tested for glucose tolerance during pregnancy had detailed anthropometry performed at birth and annually thereafter. At 5 years, plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
109
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(119 citation statements)
references
References 31 publications
(29 reference statements)
10
109
0
Order By: Relevance
“…Numerous previous studies have indicated that maternal diabetes during pregnancy has both short- and long-term adverse effects on offspring [10][11][12][13][14][15]. Metzger and co-workers [26] reported that the frequency of IGT was increased in the adolescent offspring of diabetic mothers and established the hypothesis that ''diabetes begets diabetes'', indicating that the intrauterine environment and the altered glucose regulation in the second and third trimesters absolutely influenced the short-and long-term health of the foetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous previous studies have indicated that maternal diabetes during pregnancy has both short- and long-term adverse effects on offspring [10][11][12][13][14][15]. Metzger and co-workers [26] reported that the frequency of IGT was increased in the adolescent offspring of diabetic mothers and established the hypothesis that ''diabetes begets diabetes'', indicating that the intrauterine environment and the altered glucose regulation in the second and third trimesters absolutely influenced the short-and long-term health of the foetus.…”
Section: Discussionmentioning
confidence: 99%
“…The frequent occurrence of perinatal morbidities such as macrosomia, injuries of the brachial plexus, neonatal hypoglycaemia, and foetal distress in offspring also results from glucose intolerance during gestation [7]. Furthermore, a number of epidemiological studies have demonstrated that altered glucose metabolism in mothers during pregnancy has both short-and long-term adverse effects on their offspring [10][11][12][13][14][15]. Pedersen and Freinkel established the theory of fuel-mediated teratogenesis, in which the intrauterine environment is influenced by excessive maternal fuels, which may have short-and long-term adverse effects on offspring [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…These have generally examined disease outcomes in men and/or women in relation to the birthweight of their children. Diabetes in fathers, for example, is associated with lower offspring birthweight [5][6][7][8][9]. The opposite is true for diabetes in mothers, because gestational diabetes causes fetal macrosomia [10,11].…”
mentioning
confidence: 99%
“…The Parthenon Study showed for the first time that maternal diabetes programmes neuroendocrine stress responses in the offspring, suggesting that this may be one of the pathways for their greater cardiovascular risk 47 . Even in the offspring of non-diabetic parents, both maternal and paternal insulin concentrations were positively associated with offspring adiposity and insulin resistance 45 . Thus in India, widespread maternal under nutrition with specific micronutrient deficiencies as well as high rates of gestational hyperglycaemia may programme offspring cardiometabolic disease risk, suggesting a dual teratogenesis 48 .…”
Section: Long-term Programming Effects Of Maternal Glycaemia -Evidencmentioning
confidence: 99%
“…The Parthenon study showed that, as expected, neonates of GDM mothers were heavier, longer and more adipose than control babies (offspring of non-GDM mother and non-diabetic father) 45 . There was a clustering of cardiovascular risk markers, including adiposity, higher glucose and insulin concentrations, insulin resistance (based on homeostasis model assessment for insulin resistance; HOMA-IR) and blood pressure in ODM during childhood and adolescence (Figure 2) 45-47 .…”
Section: Long-term Programming Effects Of Maternal Glycaemia -Evidencmentioning
confidence: 99%